Perempuan Korban Kekerasan Berbasis Gender dalam Novel Orang-Orang Blanti Karya Wisran Hadi - Iswadi Bahardur (Ideas Publishing, 2023)
This research is motivated by the problem of gender-based violence against women which is represented again by Wisran Hadi in the novel Orang-orang Blanti. Based on the urgency of reviewing this problem, this study aims to analyze the forms of acts of violence experienced by the female characters in the novel and their actions as an effort to resist. The research method used to study these problems is a qualitative method with descriptive content analysis techniques. The findings of the research show that a) the acts of violence experienced by the female characters in the novel Orang-orang Blanti include physical violence and psychological violence; and b) the efforts of female leaders to fight against this act of violence by tracing the background of the perpetrator s actions, rewriting the victim s biography, and rejecting socio-cultural policies that harmed her.